2001
DOI: 10.4322/rbcv.2015.240
|View full text |Cite
|
Sign up to set email alerts
|

Topografia do cone medular no lobo-guará (Chrysocyon brachyurus llliger, 1815)

Abstract: ResumoVisando o conhecimento da topografia do cone medular, foram dissecados cinco lobos guará ( Chrysocyon brachyurus) adultos, três machos e duas fêmeas, tendo sido verificado que o comprimento médio daquela porção da medula espinhal foi de cerca de 6,5 em. A base do cone medular, formada pelo sexto segmento lombar da medula espinhal, mostrou-se apoiada sobre a terceira vértebra lombar (L3) e seu ápice, mais freqüentemente, sobre a quinta vértebra lombar (L5) ou, em igual proporção, sobre a junção entre a qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
23

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 1 publication
0
7
0
23
Order By: Relevance
“…However, Fletcher (2013) observed that in dogs with a body mass less than 7 kg, the spinal cord can extend more caudally to the level of S1 vertebrae. Furthermore, the length of the conus (8.5 6 1.5 cm) in both species dissected was greater than the C. brachyurus (6.5 cm, Machado et al, 2002) and A. microtis (3.9 cm, Saldanha et al, 2011). If considered that the C. brachyurus was described as largest South American wild canid and C. thous, P. gymnocercus and A. microtis as a smaller wild canids, these data permitted consider that the length of the conus in wild canids is related to the size or weight of the animal, as described in dogs (Fletcher, 2013) and observed by Souza Junior et al (2014).…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…However, Fletcher (2013) observed that in dogs with a body mass less than 7 kg, the spinal cord can extend more caudally to the level of S1 vertebrae. Furthermore, the length of the conus (8.5 6 1.5 cm) in both species dissected was greater than the C. brachyurus (6.5 cm, Machado et al, 2002) and A. microtis (3.9 cm, Saldanha et al, 2011). If considered that the C. brachyurus was described as largest South American wild canid and C. thous, P. gymnocercus and A. microtis as a smaller wild canids, these data permitted consider that the length of the conus in wild canids is related to the size or weight of the animal, as described in dogs (Fletcher, 2013) and observed by Souza Junior et al (2014).…”
Section: Discussionmentioning
confidence: 79%
“…Relatively the length of intumescentia lumbalis the mean evaluated in both species was 3.15 6 0.65 cm, similarly to described by Souza Junior et al (2014), suggesting that the intumescentia was proportionally more short than others carnivores, as cat (3.5-4 cm, Silva et al, 2008). Third, the topography of the conus medullaris in P. gymnocercus and C. thous (L5-S3) was similarly to A. microtis (L7-S3, Saldanha et al, 2011), but differ from others canids, as dog (L3-6 or 7 vertebrae, Santiago, 1974;Evans and De Lahunta, 2010), and C. brachyurus (L3-6, Machado et al, 2002). However, Fletcher (2013) observed that in dogs with a body mass less than 7 kg, the spinal cord can extend more caudally to the level of S1 vertebrae.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Em carnívoros, tais como: o lobo-guará (Chrysocyon brachyurus), o cone medular apresenta a base em L3 e ápice em L5 [8], a irara (Eira barbara), possui base do cone em L3-L4 e ápice em L6 [1], a ariranha (Pteronura brasiliensis), tem a base em L2 e ápice em L4 [10] e o guaxinim (Procyon cancrivorus), apresenta a base em L4 e ápice em L7 [21]. Em relação ao ratão-do-banhado (Myocastor coypus), uma espé-cie de roedor, também se observou uma semelhança, o qual possui a base do cone em L3-L5 e ápice em L4-L6 [10].…”
Section: Animalunclassified
“…O valor médio do comprimento do cone medular da espécie Callithrix jacchus (1,4 cm) se apresentou mais próximo ao obtido para o ratão-do-banhado, o qual apresentou um valor médio de 2,0 cm [10], o macaco-prego, no qual foi encontrado valor médio de 2,47 [4], e a preguiça, que apresentou 2,7 cm [7], e significativamente menor do que as médias obtidas para o cachorro-do-mato (10,13 cm) [14], para o cachorro--do-mato-de-orelhas-pequenas (3,9 cm) [15], para o sauim (5,38 cm) [13], para o quati, que apresentou valor de 5,2 a 5,8 cm [5], para o macaco-de-cheiro (3,3 cm) [6], para a paca (3,39 cm) [18], para o javali (Sus serofa serofa), com valor de 3,4 cm [17], para o lobo-marinho (4,4 cm) [9], para o gato mourisco (5 cm) [3], para a ariranha (5,5 cm) [11], para a irara (4,31 cm) [1], para a jaguatirica (8,5 cm) [2], para o guaxinim (5,1 -5,6 cm) [21] e para o lobo-guará (6,5 cm) [8].…”
Section: Animalunclassified